Phased Antenna Arrays, Software Defined Radio and Artificial Intelligence: Advancing LEO Satellite Communications - ADOMNITEI, C.-I.; LESANU, C.-E.; DONE, A.; COCA, E.; LAVRIC, A. (Advances in Electrical and Computer Engineering)
This article explores how phased antenna arrays can enhance Low Earth Orbit (LEO) satellite reception systems, while addressing cybersecurity challenges in wireless communications. A conceptual design is proposed to tackle the variable dynamics of LEO satellites and meet the increasing demands of satellite communication systems for future wireless applications. The study highlights the advantages of this approach over traditional beamsteering methods. Integrating advanced artificial intelligence (AI), digital signal processing (DSP), and software-defined radio (SDR) is identified as a transformative strategy, improving adaptability and optimization for phased antenna arrays, particularly in mitigating RF threats. Beamforming evaluations demonstrate how adjusting the phases and amplitudes of feeding signals significantly impacts radiation patterns, enhancing the quality of received signals. The paper's main contribution lies in its comprehensive analysis of key challenges in LEO satellite communications, emphasizing the role of phased antenna arrays alongside AI and SDR. As cyber threats rise, the findings underscore the urgent need for further research into RF protection to secure communication systems in the rapidly evolving landscape of IoT and satellite technologies.